English plus: for asian students - Joven, Jose R. (Mandaluyong City: National Bookstore, 2007)
common phrase in englsh
Includes bibliographical references.
Keywords: A glimpse at basic grammar and syntax -- Learning competencies; Language function -- Learning competencies; Vocabulary building -- Importance of building vocabularies